Assessing Market Power, Impact of Import Tariff Reductions and Weakening Demand for Rubber Products (HS code 4011) in the Australian Market - Zainuddin, Zainuddin; Sinaga, Bonar M.; Hartoyo, Sri; Erwidodo, Erwidodo (International Journal of Economics and Financial Issues, 2019)
The purpose of this research is 1) to compare the market power of the rubber product industry (HS code 4011) between Australia and similar industries from the exporting country; 2) to analyze the impact of import tariff reduction on rubber product trade especially price, demand, export, import, export value and import value of rubber product for exporting country and importing country; and 3) to analyze the impact of weakening the demand of importing countries on the trade of rubber products (tire) especially price, demand, export, import, export value and import value for exporting country and importing country. The ability of exporters of Indonesian rubber products for mark-up prices is lower than similar industry capabilities from Thailand, China and Japan, but higher than similar industries in Australia. The decline in import tariffs has the effect of lowering import prices of rubber products in Australia, as well as export prices of rubber products from exporting countries to export markets in Australia. The decline in import tariffs for rubber products provides more benefits received by China, Thailand and Indonesia compared to benefits received by Japan and similar industries from Australia. The decline in tariffs on rubber products on the condition of weakening demand has an impact on the decline in import prices and consumer prices of these products. Export prices of rubber products from exporting countries tend to decrease if market demand weakens, and production of domestic rubber products in Australia also decreased. Keywords: market power, rubber product, import tariff, weakening demand JEL Classifications: F12, F17, L13 DOI: https://doi.org/10.32479/ijefi.6893